Characterization of Nuclear Progesterone Receptor Isoforms in the Term Equine Placenta - Nagy, Ahmed M.; Sathe, Swanand R.; Atta, Attia H.; Hammam, Abdel Mohsen M.; Hsu, Walter H. (Frontiers in Veterinary Science, 2021)
In equine parturition, the role of progestins along with the nuclear progesterone receptor (nPR) signaling pathway in the placenta is not completely clarified. The progestins play an integral role in maintaining myometrial quiescence during the late stage of pregnancy via acting on nPR isoforms (PRA and PRB; PRB is more active than PRA). The current study aimed to determine the PRA and PRB expressions in the term equine placenta at the gene and protein levels. Six term equine placentas were used in this study. Reverse transcription polymerase chain reaction (RT-PCR) was used to quantify the mRNA expression for PRA and PRB. The protein expression was detected using the Western Blot technique. The results revealed that the mRNA and protein expressions for PRA were significantly higher (P<0.0001) in the term equine placental tissue compared to the mRNA and protein expressions of PRB. These results demonstrated that nPRs are detectable in the term placenta of mares and PRA is the dominant isoform expressed. The present findings raised the possibility that the PRA plays an important role in the parturition process and expulsion of the placenta in mares.